2021
DOI: 10.1111/aor.13931
|View full text |Cite
|
Sign up to set email alerts
|

A bi‐centric experience of extracorporeal carbon dioxide removal (ECCO2R) for acute hypercapnic respiratory failure following allogeneic hematopoietic stem cell transplantation

Abstract: Despite recent improvements, non-relapse mortality due to toxic, infectious, and immunologic complications remains a substantial risk following allogeneic hematopoietic stem cell transplantation (HSCT). 1 In fact, up to every third HSCT recipient requires admission to the intensive care unit (ICU) at least once during his/her peri-or post-transplant course. 2 Pulmonary organ dysfunction presenting as an acute hypoxemic respiratory failure (ie, the acute respiratory distress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Additional file 1 : Table S3 shows the parameters available for each included study. Risk of bias assessment (Robins-I tool) revealed 4 studies with a low risk [ 31 , 34 36 ], 14 with moderate risk [ 6 , 8 , 19 , 30 , 33 , 37 44 ], and 30 with serious risk [ 4 , 18 , 21 29 , 32 , 45 60 ]. Three studies were categorized as critical risk [ 61 63 ] (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Additional file 1 : Table S3 shows the parameters available for each included study. Risk of bias assessment (Robins-I tool) revealed 4 studies with a low risk [ 31 , 34 36 ], 14 with moderate risk [ 6 , 8 , 19 , 30 , 33 , 37 44 ], and 30 with serious risk [ 4 , 18 , 21 29 , 32 , 45 60 ]. Three studies were categorized as critical risk [ 61 63 ] (Additional file 1 : Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…To date, there is little data on the frequency of use of extracorporeal lung assist devices in HSCT recipients. Two centers also involved in this study recently analyzed the use of ECCO2R systems and reported their use in 3.4% of all critically ill HSCT recipients during the observation period [18].…”
Section: Discussionmentioning
confidence: 99%